The Care and Shelter of Children and Adolescents in Brazil: Expressions of Social Issues - Maria Lúcia T. Garcia; Cristiane Bonfim Fernandez (Social Work & Society, 2009)
The world over is experiencing an increase in the numbers of children who need care. The existence of children in need of care is not peculiar to contemporary Botswana society, it also prevailed in traditional Tswana society. What has changed is the volume of children who need care, and the resources available for their care. Like other African countries, Botswana is going through a process of rapid social, economic and cultural change. One of the characteristics of this change is the disintegration of the extended family. Consequently, the extended family can no longer cope with both the quality and quantity of care that children in need of care require (Botswana Human Development Report/BHDR 2000).